Institutional Profiles: Some Strategic Tools - Frans van Vught; Jeroen Huisman (Universidad de Deusto, 2014)
In this paper we argue that both internal and external pressures and conditions urge contemporary higher education institutions to carefully think through their institutional profiles positions in domestic and global higher education contexts. We subsequently analyse strategic positioning from the strategic management literature and offer four tools - mapping, multi-dimensional ranking, benchmarking and degree profiling - to assist higher education institutions in their profiling and positioning strategies.